Silicon etch with chromium ions generated by a filtered or non-filtered cathodic arc discharge. Issue 1 (1st December 2016) - Scopece, Daniele; Döbeli, Max; Passerone, Daniele; Maeder, Xavier; Neels, Antonia; Widrig, Beno; Dommann, Alex; Müller, Ulrich; Ramm, Jürgen
Abstract: The pre-treatment of substrate surfaces prior to deposition is important for the adhesion of physical vapour deposition coatings. This work investigates Si surfaces after the bombardment by energetic Cr ions which are created in cathodic arc discharges. The effect of the pre-treatment is analysed by X-ray diffraction, Rutherford backscattering spectroscopy, scanning electron microscopy and in-depth X-ray photoemission spectroscopy and compared for Cr vapour produced from a filtered and non-filtered cathodic arc discharge. Cr coverage as a function of ion energy was also predicted by TRIDYN Monte Carlo calculations. Discrepancies between measured and simulated values in the transition regime between layer growth and surface removal can be explained by the chemical reactions between Cr ions and the Si substrate or between the substrate surface and the residual gases. Simulations help to find optimum and more stable parameters for specific film and substrate combinations faster than trial-and-error procedure. Abstract :